Technical note: Quantification of ultrafine particle mass deposition in an in vitro air-liquid interface exposure system - Anusmita Das; Mathilde Noemie Delaval; Mika Ihalainen; Jürgen Schnelle-Kreis; Anja Huber; Elias J. Zimmermann; Sebastiano Di Bucchianico; Olli Sippula; Hendryk Czech; Martin Sklorz; Ralf Zimmermann (Journal of Aerosol Science, 2026)

High concentrations of Printex 90 carbon black ultrafine particles disturb the epithelial barrier in human primary respiratory mucosa models - Totta Ehret Kasemo; Maximilian Oppmann; Sofia Dembski; Maria Steinke; Elena Lajtha; Helena Moratin; Manuel Stöth; Agmal Scherzad; Mathilde Noémie Delaval; Ralf Zimmermann; Sebastiano Di Bucchianico; Stephan Hackenberg; et al. (Environmental Toxicology and Pharmacology, 2025)

Corrigendum to “Generation, characterization, and toxicological assessment of reference ultrafine soot particles with different organic content for inhalation toxicological studies” [Sci. Total Environ. Volume 951 (2024) 175727] - Anusmita Das; Jana Pantzke; Seongho Jeong; Elena Hartner; Elias J. Zimmermann; Nadine Gawlitta; Svenja Offer; Deeksha Shukla; Anja Huber; Narges Rastak; Arūnas Meščeriakovas; Natalia P. Ivleva; et al. (Science of The Total Environment, 2024)

Generation, characterization, and toxicological assessment of reference ultrafine soot particles with different organic content for inhalation toxicological studies - Anusmita Das; Jana Pantzke; Seongho Jeong; Elena Hartner; Elias J. Zimmermann; Nadine Gawlitta; Svenja Offer; Deeksha Shukla; Anja Huber; Narges Rastak; Arūnas Meščeriakovas; Natalia P. Ivleva; et al. (Science of The Total Environment, 2024)

Toxic metals and essential trace elements in placenta and their relation to placental function - Marijke Grundeken; Klara Gustin; Marie Vahter; Mathilde Delaval; Malin Barman; Anna Sandin; Ann-Sofie Sandberg; Agnes E. Wold; Karin Broberg; Maria Kippler (Environmental Research, 2024)

Toxicity of particles derived from combustion of Ethiopian traditional biomass fuels in human bronchial and macrophage-like cells - Sarah McCarrick; Mathilde N. Delaval; Ulrike M. Dauter; Annette M. Krais; Anastasiia Snigireva; Asmamaw Abera; Karin Broberg; Axel C. Eriksson; Christina Isaxon; Anda R. Gliga (Archives of Toxicology, 2024)
The combustion of traditional fuels in low-income countries, including those in sub-Saharan Africa, leads to extensive indoor particle exposure. Yet, the related health consequences in this context are understudied. This study aimed to evaluate the in vitro toxicity of combustion-derived particles relevant for Sub-Saharan household environments. Particles ( NIST 2975) served as reference particles. The highest levels of particle-bound polycyclic aromatic hydrocarbons (PAHs) were found in wood (3219 ng/mg), followed by dung (618 ng/mg), charcoal (136 ng/mg) and DEP (118 ng/mg) (GC–MS). BEAS-2B bronchial epithelial cells and THP-1 derived macrophages were exposed to particle suspensions (1–150 µg/mL) for 24 h. All particles induced concentration-dependent genotoxicity (comet assay) but no pro-inflammatory cytokine release in epithelial cells, whereas dung and wood particles also induced concentration-dependent cytotoxicity (Alamar Blue). Only wood particles induced concentration-dependent cytotoxicity and genotoxicity in macrophage-like cells, while dung particles were unique at increasing secretion of pro-inflammatory cytokines (IL-6, IL-8, TNF-α). In summary, particles derived from combustion of less energy dense fuels like dung and wood had a higher PAH content and were more cytotoxic in epithelial cells. In addition, the least energy dense and cheapest fuel, dung, also induced pro-inflammatory effects in macrophage-like cells. These findings highlight the influence of fuel type on the toxic profile of the emitted particles and warrant further research to understand and mitigate health effects of indoor air pollution.

Assessment of the oxidative potential of nanoparticles by the cytochrome c assay: assay improvement and development of a high-throughput method to predict the toxicity of nanoparticles - Mathilde Delaval; Wendel Wohlleben; Robert Landsiedel; Armelle Baeza-Squiban; Sonja Boland (Archives of Toxicology, 2017)